Afecções cirúrgicas do sistema urinário de cães e gatos atendidos no Hospital Veterinário da Universidade Federal do Pará (2017-2023) - MONTEIRO, Alanna Maria de Oliveira (2024)
This study offers a comprehensive analysis of surgical conditions of the urinary system in dogs and cats treated at the University Veterinary Hospital of the Federal University of Pará between January 2017 and December 2023. Data from medical records of animals undergoing surgical procedures were analyzed, including date of care, species, age, sex, race, diagnosis of the condition and surgical procedure. In total, 49 animals were diagnosed with urinary system disorders, with 56 surgical procedures performed, corresponding to 3.19% of the total surgeries performed by the Veterinary Hospital. Of the urinary system procedures, 54% of cases involved canines and 46% felines. Cystolithiasis was the most prevalent condition, accounting for 69% of cases, followed by urethral obstruction, which accounted for 9%. Cystotomies were the most frequent surgeries, corresponding to 72% of procedures, followed by urethrostomies, with 11% of cases. These results highlight the relevance of university veterinary hospitals in teaching, research and extension, in addition to highlighting the importance of advances in veterinary nephrology and their contribution to the promotion of animal health.